Restoration at the Rocky Mountain Arsenal National Wildlife Refuge - Arthur, Denise T., author; Redente, E. F., advisor; Seastadt, T. R, committee member; Barbarick, K. A., committee member; Paschke, Mark, committee member (Colorado State University. Libraries, 2000)
Two ecological restoration studies were implemented in 1995 and continued through 1997 on the Rocky Mountain Arsenal National Wildlife Refuge (Refuge). The Refuge is 17 square km and is located 10 km northeast of Denver, Colorado. The studies were initiated to identify restoration practices that could accelerate the establishment of late serai perennial plant communities on areas of the Refuge dominated by exotic species. The long-term goal for the site is to restore the entire Refuge to native prairie in order to provide diverse habitat for the variety of wildlife that reside on the Refuge. A number of research objectives were developed to provide specific restoration information. The following are the objectives addressed by the research: 1) determine if supplemental water improves establishment of warm and cool season perennial species; 2) determine if supplemental water, in combination with sucrose, accelerates the establishment of native prairie species by reducing the time that weedy species dominate a revegetated site; 3) determine the effect of mulch or a cover crop on native species establishment; 4) determine the effect of seeding technique (drill vs. broadcast) on native species establishment; and 5) determine the effect of carbon (sucrose) and nitrogen additions with supplemental water on native species colonization in weed infested areas. The Crested Wheatgrass Replacement Study and the Nitrogen Sucrose Study assessed plant community development over a three year period. Both studies assessed a number of restoration practices including: irrigation, seeding technique (drill vs. broadcast), mulch treatments, and the application of a carbon (sucrose) or a nitrogen (fertilizer) soil amendment Results from the Crested Wheatgrass Replacement Study showed that increased irrigation had a two-fold benefit to native restoration. Irrigation played an important role in the successful establishment of native perennial species and inhibited the growth of early-seral weedy species. Broadcast seeding doubled perennial species biomass and decreased annual species biomass by 20 % when compared to drill seeding. Mulch application improved perennial forb biomass but perennial grass biomass and biomass of annual species was the same with and without mulch. The cover crop treatment was not an effective treatment, and resulted in low perennial species biomass, and high annual forb biomass, compared to the mulch and no mulch treatments. The sucrose applications showed no clear benefit in overall perennial production or a decrease in annual or perennial production. Plant available soil nitrogen (N) decreased with addition of sucrose compared to those sites not amended, however, there was no significant plant community response to the lower plant available soil nitrogen. The Nitrogen Sucrose Study showed that two years of irrigation in combination with three years of sucrose applications improved perennial forb and grass production. Irrigation in combination with nitrogen amendments during the same period did not increase perennial grass production but greatly increased annual forb production over plots receiving sucrose. The nitrogen plus irrigation plots shifted community structure toward one dominated by annuals while the sucrose and irrigation plots shifted community structure toward a later serai com m unity dominated by perennial grasses. In general the two studies demonstrate that with the use of various restoration techniques perennial community development can be enhanced and provides insight into how nutrient availability may be important in observed shifts in community structure.
Keywords: ecology; range management; environmental engineering